Cybersecurity Awareness and Practices Among Criminal Justice Students in One Higher Educational Institution in Cordillera - Rufino, Claire; Moyao, Warren (Technium Social Sciences Journal, 2025)
Cybersecurity has emerged as an essential component of contemporary living in the digital realm, where practically all transactions, including those of students, occur online. The study attempts to determine the present degree of student awareness to potentially identify cybersecurity vulnerabilities in their operations. A survey employing Likert-scale questions was conducted among college students pursuing criminal justice degrees to assess their cybersecurity understanding, experiences, and practices. The acquired data were analyzed via descriptive statistics. Students exhibit a considerable understanding of established cybersecurity issues; yet they continue to engage in minor problematic behaviors, particularly with social networking, which remains susceptible to exploitation by cyber offenders. Consequently, additional efforts are encouraged not only to promote awareness but also to translate awareness of cybersecurity issues into tangible behaviors.